In Liddle Syndrome, Epithelial Sodium Channel Is Hyperactive Mainly in the Early Part of the Aldosterone-Sensitive Distal Nephron - Nesterov, Viatcheslav; Krueger, Bettina; Bertog, Marko; Dahlmann, Anke; Palmisano, Ralf; Korbmacher, Christoph (Hypertension)
The epithelial sodium channel (ENaC) is rate limiting for Na(+) absorption in the aldosterone-sensitive distal nephron comprising the late distal convoluted tubule (DCT2), the connecting tubule (CNT), and the entire collecting duct. Liddle syndrome (pseudohyperaldosteronism), a severe form of salt-sensitive hypertension, is caused by gain-of-function mutations of ENaC, but the precise tubular site of increased ENaC function is unknown. In the cortical collecting duct (CCD), ENaC is known to be regulated by aldosterone. In contrast, we recently reported aldosterone-independent ENaC regulation in the early part of the aldosterone-sensitive distal nephron. Here, we investigated ENaC function in the transition zone of DCT2/CNT or CNT/CCD microdissected from mice homozygous for Liddle syndrome mutation or from wild-type control mice. Whole-cell patch-clamp recordings were used to measure amiloride-sensitive ENaC currents in nephron fragments from mice maintained on different sodium diets to vary plasma aldosterone levels. Our data indicate that in mice with Liddle syndrome, the primary site of increased Na(+) reabsorption is the DCT2/CNT. In addition, increased aldosterone responsiveness of ENaC in CNT/CCD may contribute to salt-sensitive hypertension in Liddle syndrome. Single channel properties of ENaC were similar in Liddle syndrome mutation and wild-type mice, but ENaC expression at the apical membrane was increased in Liddle syndrome mutation when compared with wild-type mice, in particular, in animals maintained on a high salt diet. Our findings highlight the importance of ENaC function and regulation in the early part of the aldosterone-sensitive distal nephron for the maintenance of sodium balance and blood pressure control.

Inside Cover: Structure–Reactivity Relationship in the Frustrated Lewis Pair (FLP)‐Catalyzed Hydrogenation of Imines (Chem. Eur. J. 22/2016) - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Inside Cover: Structure-Reactivity Relationship in the Frustrated Lewis Pair (FLP)-Catalyzed Hydrogenation of Imines (Chem. Eur. J. 22/2016) - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry - A European Journal)

Improved rf design using precise 3d near-field measurements and near-field to far-field transformations - Hangmann, C; Mager, T; Khan, S; Hedayat, C; Hilleringmann, Ulrich (Smart System Integration-International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Precession and nutation dynamics of nonlinearly coupled non-coaxial three-dimensional matter wave vortices - Driben, R.; Konotop, V. V.; Meier, Torsten (Scientific Reports)
Nonlinearity is the driving force for numerous important effects in nature typically showing transitions between different regimes, regular, chaotic or catastrophic behavior. Localized nonlinear modes have been the focus of intense research in areas such as fluid and gas dynamics, photonics, atomic and solid state physics etc. Due to the richness of the behavior of nonlinear systems and due to the severe numerical demands of accurate three-dimensional (3D) numerical simulations presently only little knowledge is available on the dynamics of complex nonlinear modes in 3D. Here, we investigate the dynamics of 3D non-coaxial matter wave vortices that are trapped in a parabolic potential and interact via a repulsive nonlinearity. Our numerical simulations demonstrate the existence of an unexpected and fascinating nonlinear regime that starts immediately when the nonlinearity is switched-on and is characterized by a smooth dynamics representing torque-free precession with nutations. The reported motion is proven to be robust regarding various effects such as the number of particles, dissipation and trap deformations and thus should be observable in suitably designed experiments. Since our theoretical approach, i.e., coupled nonlinear Schrödinger equations, is quite generic, we expect that the obtained novel dynamical behavior should also exist in other nonlinear systems.

Interactively controlled quad remeshing of high resolution 3D models - Ebke, Hans-Christian; Schmidt, Patrick; Campen, Marcel; Kobbelt, Leif (ACM Transactions on Graphics)
Parametrization based methods have recently become very popular for the generation of high quality quad meshes. In contrast to previous approaches, they allow for intuitive user control in order to accommodate all kinds of application driven constraints and design intentions. A major obstacle in practice, however, are the relatively long computations that lead to response times of several minutes already for input models of moderate complexity. In this paper we introduce a novel strategy to handle highly complex input meshes with up to several millions of triangles such that quad meshes can still be created and edited within an interactive workflow. Our method is based on representing the input model on different levels of resolution with a mechanism to propagate parametrizations from coarser to finer levels. The major challenge is to guarantee consistent parametrizations even in the presence of charts, transition functions, and singularities. Moreover, the remaining degrees of freedom on coarser levels of resolution have to be chosen carefully in order to still achieve low distortion parametrizations. We demonstrate a prototypic system where the user can interactively edit quad meshes with powerful high-level operations such as guiding constraints, singularity repositioning, and singularity connections.

Bijective maps from simplicial foliations - Campen, Marcel; Silva, Cláudio T.; Zorin, Denis (ACM Transactions on Graphics)
This paper presents a method for bijective parametrization of 2D and 3D objects over canonical domains. While a range of solutions for the two-dimensional case are well-known, our method guarantees bijectivity of mappings also for a large, combinatorially-defined class of tetrahedral meshes (shellable meshes). The key concept in our method is the piecewise-linear (PL) foliation, decomposing the mesh into one-dimensional submanifolds and reducing the mapping problem to parametrization of a lower-dimensional manifold (a foliation section). The maps resulting from these foliations are proved to be bijective and continuous, and shown to have provably bijective PL approximations. We describe exact, numerically robust evaluation methods and demonstrate our implementation's capabilities on a large variety of meshes.

Influence of strong screening effect on the perpendicular polarized linear excitonic absorption spectra of semiconducting carbon nanotubes - Meier, Torsten; Liu, Hong (The European Physical Journal B)
For incident light polarized perpendicular to the tube axis the multi-band semiconductor Bloch equations (MB-SBEs) that involve various screened interband Coulomb interactions (ICIs) are derived. The calculated E 12 peak is very close to the longitudinal excitonic peak E 22. Compared with the previous theoretical peak positions, the blue-shift of the peak in our results is about 0.5 eV. Then, subsequent detailed analyses show that the screening effect on the diagonal ICIs (D-ICIs) plays a key role in this big blue-shift. The valley-degenerate transverse pair excitations holding the same selection rule further enhance the screening effect on D-ICIs. Specially at q = 0 the dielectric function acting on the D-ICIs enhances two times. In our calculation the strong screening effect contributes 90% of the big blue-shift, while the non-diagonal ICIs (ND-ICIs) contribute to 10% of the blue-shift.

Changes in dietary intake during puberty and their determinants: results from the GINIplus birth cohort study - Harris, Carla; Flexeder, Claudia; Thiering, Elisabeth; Buyken, Anette; Berdel, Dietrich; Koletzko, Sibylle; Bauer, Carl-Peter; Brüske, Irene; Koletzko, Berthold; Standl, Marie (BMC Public Health)
Background Understanding changes in dietary intake during puberty could aid the mapping of dietary interventions for primary prevention. The present study describes dietary changes from childhood to adolescence, and their associations with parental education, family income, child education, body mass index (BMI), pubertal onset and screen-time sedentary behaviour. Methods Dietary data (n = 1232) were obtained from food frequency questionnaires at the 10- and 15-year follow-ups of the GINIplus birth cohort study. Intakes of 17 food groups, macronutrients and antioxidant vitamins, were described by a) paired Wilcoxon rank sum tests, comparing average intakes at each time-point, and b) Cohen’s kappa “tracking” coefficients, measuring stability of intakes (maintenance of relative tertile positions across time). Further, associations of changes (tertile position increase or decrease vs. tracking) with parental education, family income, child education, pubertal onset, BMI, and screen-time, were assessed by logistic regression and multinomial logistic regression models stratified by baseline intake tertile. Results Both sexes increased average intakes of water and decreased starchy vegetables, margarine and dairy. Females decreased meat and retinol intakes and increased vegetables, grains, oils and tea. Males decreased fruit and carbohydrates and increased average intakes of meat, caloric drinks, water, protein, fat, polyunsaturated fatty acids (PUFAs), vitamin C and alpha-tocopherol. Both sexes presented mainly “fair” tracking levels [κw = 0.21–0.40]. Females with high (vs. low) parental education were more likely to increase their nut intake [OR = 3.8; 95 % CI = (1.7;8.8)], and less likely to decrease vitamin C intakes [0.2 (0.1;0.5)], while males were less likely to increase egg consumption [0.2 (0.1;0.5)] and n3 PUFAs [0.2 (0.1;0.5)]. Females with a higher (vs. low) family income were more likely to maintain medium wholegrain intakes [0.2 (0.1;0.7) for decrease vs. tracking, and 0.1 (0.0;0.5) for increase vs. tracking], and were less likely to decrease vitamin C intakes [0.2 (0.1;0.6)]. Males with high education were less likely to increase sugar-sweetened foods [0.1 (0.1;0.4)]. Finally, BMI in females was negatively associated with decreasing protein intakes [0.7 (0.6;0.9)]. In males BMI was positively associated with increasing margarine [1.4 (1.1;1.6)] and vitamin C intakes [1.4 (1.1;1.6)], and negatively associated with increasing n3 PUFA. Conclusions Average dietary intakes changed significantly, despite fair tracking levels, suggesting the presence of trends in dietary behaviour during puberty. Family income and parental education predominantly influenced intake changes. Our results support the rationale for dietary interventions targeting children, and suggest that sex-specific subpopulations, e.g. low socio-economic status, should be considered for added impact.
Keywords: Puberty; Dietary intake; Dietary changes; Tracking; Determinants; Epidemiology

Pushing the Limits of Instance Matching Systems: A Semantics-Aware Benchmark for Linked Data - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Herschel, Melanie; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Conference on World Wide Web Companion, WWW 2015, Florence, Italy, May 18-22, 2015 - Companion Volume)

CubeViz: Exploration and Visualization of Statistical Linked Data - Martin, Michael; Abicht, Konrad; Stadler, Claus; Ngonga Ngomo, Axel-Cyrille; Soru, Tommaso; Auer, Sören (Proceedings of the 24th International Conference on World Wide Web Companion, WWW 2015, Florence, Italy, May 18-22, 2015 - Companion Volume)

ROCKER: A Refinement Operator for Key Discovery - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Conference on World Wide Web, WWW 2015, Florence, Italy, May 18-22, 2015)

GERBIL: General Entity Annotator Benchmarking Framework - Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille; Baron, Ciro; Both, Andreas; Brümmer, Martin; Ceccarelli, Diego; Cornolti, Marco; Cherix, Didier; Eickmann, Bernd; Ferragina, Paolo; Lemke, Christiane; et al. (Proceedings of the 24th International Conference on World Wide Web, WWW 2015, Florence, Italy, May 18-22, 2015)

Gesellschaftliche und kulturelle Bedeutung von Mittagsverpflegung in Gießener Kindertagesstätten - Klünder, Nina (Hauswirtschaft und Wissenschaft)

Verpflegung in Kindertagesstätten gestalten – Ergebnisse einer qualitativen Studie - Meier-Gräwe, Uta; Klünder, Nina (KiTa aktuell)

Effects of human milk and formula on postprandial glycaemia and insulinaemia - Wright, C J; Atkinson, F S; Ramalingam, N; Buyken, Anette; Brand-Miller, J C (European Journal of Clinical Nutrition)

Dietary micronutrient intake during pregnancy is a function of carbohydrate quality - Goletzke, Janina; Buyken, Anette; Louie, Jimmy CY; Moses, Robert G; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

Early Diet and Later Cancer Risk: Prospective Associations of Dietary Patterns During Critical Periods of Childhood with the GH-IGF Axis, Insulin Resistance and Body Fatness in Younger Adulthood - Günther, Anke L. B.; Schulze, Matthias B.; Kroke, Anja; Diethelm, Katharina; Joslowski, Gesa; Krupp, Danika; Wudy, Stefan; Buyken, Anette (Nutrition and Cancer)

Relevance of fruits, vegetables and flavonoids from fruits and vegetables during early life, mid-childhood and adolescence for levels of insulin-like growth factor (IGF-1) and its binding proteins IGFBP-2 and IGFBP-3 in young adulthood - Krupp, Danika; Remer, Thomas; Penczynski, Katharina J.; Bolzenius, Katja; Wudy, Stefan A.; Buyken, Anette (British Journal of Nutrition)
Abstract The growth hormone (GH) insulin-like growth factor (IGF) axis has been linked to insulin metabolism and cancer risk. Experimental evidence indicates that the GH–IGF axis itself can be influenced by dietary flavonoids. As fruit and vegetable (FV) intake is a major source of flavonoid consumption, FV’s beneficial health effects may be explained via flavonoids’ influence on the GH–IGF axis, but observational evidence is currently rare. We used data from Dortmund Nutritional and Anthropometric Longitudinally Designed Study participants to analyse prospective associations between FV, fruit intake and flavonoid intake from FV (FlavFV) with IGF-1 and its binding proteins IGFBP-2 and IGFBP-3. Subjects needed to provide a fasting blood sample in adulthood (18–39 years) and at least two 3-d weighed dietary records in early life (0·5−2 years, n 191), mid-childhood (3−7 years, n 265) or adolescence (girls: 9−15 years, boys: 10−16 years, n 261). Additional analyses were conducted among those providing at least three 24-h urine samples in adolescence ( n 236) to address the predictor urinary hippuric acid (HA), a biomarker of polyphenol intake. Higher fruit intake in mid-childhood and adolescence was related to higher IGFBP-2 in adulthood ( P =0·03 and P =0·045). Comparable trends ( P =0·045−0·09) were discernable for FV intake (but not FlavFV) in all three time windows. Similarly, higher adolescent HA excretion tended to be related ( P =0·06) to higher adult IGFBP-2 levels. Regarding IGFBP-3, a marginal ( P =0·08) positive association was observed with FlavFV in mid-childhood only. None of the investigated dietary factors was related to IGF-1. In conclusion, higher fruit and FV intakes during growth may be relevant for adult IGFBP-2, but probably not for IGFBP-3 or IGF-1.

Relative validation of 24-h urinary hippuric acid excretion as a biomarker for dietary flavonoid intake from fruit and vegetables in healthy adolescents - Penczynski, Katharina J.; Krupp, Danika; Bring, Anna; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (European Journal of Nutrition)